Estágio supervisionado obrigatório iii (eso-iii) artroscopia em enfermidade degenerativa crônica de ossos carpo radial e intermédio, em equina: relato de caso. - Oliveira, Walnê de (Universidade Federal Rural do Semi-Árido, 2020)
The Supervised Internship III (ESO-III), was performed at Clínica Médica e Cirúrgica Horse-Vet: M. A. MAIA CLÍNICA VETERINÁRIA, CNPJ: 22.176.729/0001-56, located at Rua São Paulo, 45 - Bairro Mangabeira, Macaíba/RN. The internship period began on 08/18/2020 and ended on 10/16/2020, in the sectors of Medical and Surgical Clinics of Large Animals, area: Equines and sub-area: Abdomen and Locomotor, with a total workload of 240 (two hundred and forty) hours. The objective of the internship was to follow the routines of a Medical Clinic and a Surgical Center for equines, through casuistry in the period, aiming the improvement of the academic formation, through the practices of routine activities in the professional area, confronting and adding the knowledge acquired during the course, through the experience in a clinical and hospital environment. And describe an approach of a surgical case in an equine patient, 7 (seven) years old, of the quarter mile race, used in sports (vaquejada), that presented claudication, in right thoracic limb, in the region of the carpus, by means of image exams (radiographic and ultrasonographic). After several unsuccessful clinical treatments, a surgical treatment was indicated, by arthroscopy. Through the arthroscope, in real time, the interior of the articular cavity was visualized, by coupling in a visual system of lenses with a light source, erosions in the cartilages of the radial and intermediate carpal bones were verified. It is also widely used in the diagnosis and treatment of traumatic and degenerative joint diseases. The surgery was performed on September 25, 2020, in the surgical center of CLINICAT. After arthro surgery, the patient was placed in a soft-floored bay, lined with sand, and changed bandages daily. In parallel, after 7 (seven) days, 3 (three) weekly physiotherapy sessions took place, with ShockWave. Until the end of the internship period, the patient had not been discharged from hospital, which includes 120 days, to start the first training exercises. The surgical technique used in this case report required the use of special surgical equipment, which resulted in savings, low percentage of sequelae and a shorter postoperative rest time, conditions necessary for convalescence and rapid resolution of the locomotor disease addressed, when compared to conventional techniques.
Keywords: Artrocirurgia, cirurgia articular, shockwave.; Equino; Artrocospia; Cirurgia articular; Shockwave; Arthrosurgery; Equine; Arthrocospia; Joint surgery; CIENCIAS AGRARIAS::MEDICINA VETERINARIA